Pharmacological treatment of knee osteoarthritis: Special considerations of the new German guideline - Steinmeyer, Jürgen; Bock, Fritjof; Stöve, Johannes; Jerosch, Jörg; Flechtenmacher, Johannes; Justus Liebig University Giessen (My University, 2018)
The pharmacological treatment of knee osteoarthritis (OA) is a purely symptomatic therapy, which often ensures that the mobility of the patient is successfully retained. This article refers to the recommendations and opinions regarding the pharmacotherapy of knee OA contained in the new guideline of the Association of the Scientific Medical Societies in Germany (AWMF), highlighting several important aspects and describing the considerations underlying the decision-making process. With this article it is hoped that therapeutic effectiveness can be realistically estimated, that any risks of medication errors and avoidable side effects can be reduced, and that further helpful measures can be taken into consideration.
Keywords: knee; osteoarthritis; guideline; pharmacotherapy; NSAIDs; ddc:610